2020
DOI: 10.2196/19804
|View full text |Cite
|
Sign up to set email alerts
|

Public Opinion About E-Cigarettes on Chinese Social Media: A Combined Study of Text Mining Analysis and Correspondence Analysis

Abstract: Background Electronic cigarettes (e-cigarettes) have become increasingly popular. China has accelerated its legislation on e-cigarettes in recent years by issuing two policies to regulate their use: the first on August 26, 2018, and the second on November 1, 2019. Social media provide an efficient platform to access information on the public opinion of e-cigarettes. Objective To gain insight into how policies have influenced the reaction of the Chinese … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Finally, it should be taken into account that electronic cigarettes have become popular. It was reported that new communication means could be crucial for improving knowledge about this unhealthy habit [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it should be taken into account that electronic cigarettes have become popular. It was reported that new communication means could be crucial for improving knowledge about this unhealthy habit [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the division of work in the NPP control crews, junior operators are in charge of the major operational tasks in both routine and emergency situations, while senior operators are responsible for monitoring and guiding juniors' activities and adjusting their workloads through leadership actions (Wang et al, 2017, 2020). When handling simulated emergency scenarios, it was found that the communication process of the control crews was centered on the parameter changes and operational status within the scope of junior operators' work (Reinerman‐Jones et al, 2019; Wang & Gao, 2016). This is probably because to cope with emergency tasks in NPPs, the verbal communication and behavior coordination required is more from junior operators than from senior operators.…”
Section: Hypothesesmentioning
confidence: 99%